2005
DOI: 10.1107/s1600536805034732
|View full text |Cite
|
Sign up to set email alerts
|

3,5-Bis(2-hydroxyethyl)-4-oxahexacyclo[5.4.1.02,6.03,10.05,9.08,11]dodecane

Abstract: The title mol­ecule, C15H20O3, exhibits C—C bond lengths that deviate from normal values. A number of long and short C—C bonds are observed. Neighbouring mol­ecules inter­act via strong O—H⋯O hydrogen bonds, forming two‐dimensional hydrogen‐bonded sheets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 8 publications
1
9
0
Order By: Relevance
“…1). A number of publications have focused on the molecular geometries of PCU cage derivatives (Flippen-Anderson et al, 1991;Linden et al, 2005;Kruger et al, 2005), and it has been reported that these compounds exhibit C-C bond lengths deviating from the normal value of 1.54 Å .…”
mentioning
confidence: 99%
“…1). A number of publications have focused on the molecular geometries of PCU cage derivatives (Flippen-Anderson et al, 1991;Linden et al, 2005;Kruger et al, 2005), and it has been reported that these compounds exhibit C-C bond lengths deviating from the normal value of 1.54 Å .…”
mentioning
confidence: 99%
“…The C-C strained bond angles in (1) vary from 95.31 (10) to 125.21 (14) , deviating from the ideal tetrahedral angle of 109.5 . Previous studies showed that PCUD caged compounds normally display C-C bond lengths which deviate from expected value of 1.54 Å (Bott et al, 1998;Flippen-Anderson et al, 1991;Linden et al, 2005;Kruger et al, 2005). The structure of (1) also exhibits unusual Csp 3 -Csp 3 single-bond lengths ranging from 1.5092 (19) Å to 1.5935 (19) Å .…”
Section: Structural Commentarymentioning
confidence: 91%
“…For examples of PCU cage structures that exhibit C-C bond lengths that deviate from the normal value, see: Flippen-Anderson et al (1991); Linden et al (2005). For similar structures, see: Kruger et al (2005Kruger et al ( , 2006; Karpoormath et al (2010). Mo K radiation = 0.10 mm À1 T = 173 K 0.34 Â 0.22 Â 0.16 mm…”
Section: Related Literaturementioning
confidence: 99%
“…We have reported the single-crystal X-ray structure of a range of pentacycloundecane (PCU) derivatives. More recently this included an ether diol (Kruger et al, 2005), a mono-ketone ethyl acetate (Kruger et al, 2006) and a mono-ketone diester (Karpoormath et al, 2010). The tile compound is the first example of a PCU derivative X-ray structure report containing an ether, ester and primary alcohol functional groups (Fig.…”
Section: S1 Commentmentioning
confidence: 99%